Application of the CCME Water Quality index for assessment of groundwater contamination in the rural environment of the Great Hungarian Plain - MESTER, TAMÃS; BALLA, DÃNIEL; SZABÃ“, GYÃ–RGY (Journal of Soil and Water Conservation, 2020)
As a result of the establishment of sewage networks in recent decades in Hungary, the secondary public utility rate had fallen to 14% by 2017. Investments have significant impacts on the rural environment, primarily on groundwater resources. This study aims to evaluate the changes in the hydrochemical properties of groundwater after the construction of the sewage system in an eastern Hungarian settlement. Water samples were collected from 40 groundwater wells in the summer of 2013, 2017 and 2018. The groundwater quality was assessed by using the Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) method. The following parameters were used for calculation: pH, EC, NH4 +, NO2 -, NO3 -, PO4 3-, COD and Na. The results show strong groundwater contamination. According the CCME WQI in 2013, 80% of the water samples were classified as â€œmarginalâ€ or â€œpoorâ€ and only 20% as â€œfairâ€, â€œgoodâ€ or â€œexcellentâ€. In 2017 a significant improvement in water quality could be observed. The percentage of â€œmarginalâ€ or â€œpoorâ€ water samples had decreased to 55%, while the percentage of â€œfairâ€, â€œgoodâ€ or â€œexcellentâ€ water samples had increased to 45%. Although in 2018 a slight decrease in water quality was measured, the degree of contamination was still lower compared to the baseline in 2013. Based on the results, it can be concluded that the purification process is still ongoing. Groundwater purification has been slowed down by the accumulated organic matter in the soil and the fact that there are still households that have not joined the sewer network, and that point sources such as latrines and manure heaps can still be found in several parts of the settlement. Further environmental measures are needed to eliminate these sources of pollution.